Numerical Analysis and Test Research of the Dynamic Stress of Spiral Bevel Gear - Liu Haiou; Liu Xingxing (Jixie chuandong)
The inlet gearbox spiral bevel gear of aircraft turbofan engine may result in insufficient of gear vibration margin because of the limitation of structure integration. The numerical analysis and test research of the dynamic stress of spiral bevel gear are carried out. The simulation analysis of bevel gear includes modal and frequency response analysis,the vibration rules of bevel gear is studied. The dynamic stress of bevel gear under working condition is got by using the method of strain gauge in test. The result show that theoretical analysis fits well with experimental results. The methods of dynamic stress calculation and experimental test are feasible.